Alleviation of postharvest chilling injury in sweet pepper using Salicylic acid foliar spraying incorporated with caraway oil coating under cold storage - Hanaei, Saeed; Bodaghi, Hojatollah; Ghasimi Hagh, Ziba (Frontiers in Plant Science, 2022)
The decrease in the postharvest quality of sweet peppers in terms of the physiological disorders resulting from cold storage (less than 7-10 °C) results in the significant economic losses. The ability of pre-harvest foliar spraying of Salicylic acid (SA) (1.5 and 3 mM), and the postharvest caraway (Carum carvi) oil coating (0.3 % and 0.6 %) on chilling injury (CI) and the quality of stored sweet pepper at 4±2 °C for 60 d followed by an additional two days at 20 °C was investigated. The antifungal activity of caraway oil (0.15, 0.3, and 0.6 %) on Botrytis cinerea mycelia in in vitro showed that the maximum percentage of inhibition was equal to 95 % in the medium with 0.6 % of this oil. The CI of sweet pepper was significantly reduced by increasing SA, and caraway oil concentrations compared to the control, especially the lowest CI (14.36 %) was obtained at 3 mM SA and 0.6% caraway oil treatment. The results showed a significant delay in the changes of weight loss (79.43 %), firmness (30 %), pH (6 %), total soluble solids (TSS) (17 %), titratable acidity (TA) (32 %), and color surface characteristics and, capsaicin content (5 %) compared to control fruits at 3 mM SA and 0.6 % caraway oil concentrations. Results indicated that the decrease in CI was related with a decrease in electrolyte leakage, malondialdehyde (MDA) content, total phenolic production, decay incidence, and an increase in activity of antioxidant enzymes, including catalase (CAT), superoxide dismutase (SOD), and peroxidase (POD). Thus, the incorporation of SA (3 mM) and caraway oil (0.6 %) to reduce the CI of stored sweet pepper at low temperature can be considered a practical solution to improve the quality and marketability of this product.